Design and simulation of a wearable textile monopole antenna for Body Centric Wireless Communications - Hasliza, A. Rahim; Mohd. Fareq, Abd. Malek, Dr.; Ismahayati, Adam; Sahadah, Ahmad; Nur Baya, Mohd Hashim; Hall, Peter S. (The Electromagnetics Academy, 2013)
Link to publisher's homepage at http://emacademy.org/